Preparation method of PPTA composite nanofiltration membrane with pore diameter optimized by hydrogel mosaic structure
By constructing a hydrogel mosaic structure on the PPTA porous membrane and forming an IP layer using interface polymerization, the problems of uneven pore size and unstable separation performance of PPTA nanofiltration membrane are solved, and higher structural stability and performance improvement are achieved. Suitable for a variety of industrial applications.
Patent Information
- Application Number
- CN202411853602.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing PPTA nanofiltration membranes have problems of uneven pore size and unstable separation performance in water treatment, which affects its application prospects.
By constructing a hydrogel mosaic structure on the PPTA porous membrane, optimizing the pore size distribution, and using interface polymerization to form an IP layer on the surface of the base film, improving the structural stability and performance of the membrane.
It significantly improves the structural stability and pore size distribution of membrane pore size, improves permeability and retention performance, and is suitable for water treatment, biopharmaceuticals and chemical dye industries.
Smart Images

Figure CN119488818A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment filtration membranes, and in particular relates to a method for preparing a PPTA composite nanofiltration membrane with optimized pore size by utilizing a hydrogel mosaic structure. Background Art
[0002] As an important technology, water treatment filtration membrane technology is widely used in food processing, water treatment in the field of environmental protection, industrial production and many other aspects. The pore size of nanofiltration membrane is usually 0.5-2nm, so it can effectively remove multivalent ions, organic matter, trace pollutants, etc. in water, while allowing monovalent ions to pass through. It has been widely used in the current water treatment field. PPTA nanofiltration membrane is widely used in the production of softened drinking water. Nanofiltration technology is used to soften high-hardness island brackish water, and the water quality after treatment can meet the drinking water standard.
[0003] Nanofiltration membrane is a special filter membrane with high selectivity and high mobility. Its existing preparation methods are diverse, mainly including interfacial polymerization, blending, coating, layer-by-layer self-assembly, and thermal induced phase separation. The layer-by-layer self-assembly method is simple to operate, and the film-forming materials are rich. A variety of polyelectrolytes can be selected as film-forming materials to adjust the properties and functions of the membrane, and the membrane thickness is controllable. By controlling the number of deposited layers, the thickness and performance of the membrane can be precisely controlled, but when there are too many layers, the separation performance and stability of the membrane will be affected. The nanofiltration membrane prepared by interfacial polymerization has the advantages of mild preparation conditions, high production efficiency, asymmetric pore size distribution, and precise control of surface properties. In addition to preparing nanofiltration membranes, it is also used to prepare composite membranes. At present, the uneven pore size of the base membrane prepared by PEG as a porogen is a major difficulty in the application of PPTA porous membranes in water treatment and other aspects. Therefore, the development of a stable method for modifying the pore size is of great significance for the application of PPTA membranes.
[0004] Nanofiltration membrane is the core of nanofiltration technology. The essence of preparing nanofiltration membrane is to construct nano-scale pores on the surface of supporting materials through a certain way, so as to give it nanofiltration function. Interfacial polymerization technology is widely used due to its convenient, efficient and stable technical advantages. The nanofiltration membrane prepared by this method consists of two parts: selective separation membrane and base membrane. It has the characteristics of strong stability, high water flux and easy industrial production. Traditional interfacial polymerization technology uses polyamine monomers and acyl chloride monomers dissolved in oil and water phases to condense on the surface of microfiltration or ultrafiltration porous base membrane to form a dense polyamide film with a thickness of 50 to 100 nm. The film is solidified on the surface of the base membrane and plays a role in selective separation. However, TFC nanofiltration membrane still faces the problem of membrane performance (permeability, selectivity, anti-fouling, etc.), which will directly affect the separation efficiency and application cost of nanofiltration membrane, and then determine its future application prospects. For this reason, researchers have made great efforts and achieved many results in the research and development of high-performance TFC nanofiltration membranes based on interfacial polymerization technology. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and to briefly introduce some preferred embodiments.
[0006] As one aspect of the present invention, the present invention provides a method for preparing a PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure, which comprises the following steps:
[0007] Step 1: applying 2.5N4.0MPa pressure to the poly(p-phenylene terephthalamide) nanofiltration membrane base film, immersing it in a 4N10wt% precursor solution for 2 to 8 minutes, and obtaining a PPTA porous membrane; the precursor solution includes titanate or silicate;
[0008] Step 2: placing the PPTA porous membrane obtained in step 1 in an 80-95% ethanol solution for hydrolysis to obtain a PPTA porous membrane with modified pore size;
[0009] Step 3: coating a layer of silane coupling agent solution on the surface of the pore-modified PPTA porous membrane obtained in step 2;
[0010] Step 4: dissolving piperazine-2-carboxylic acid and sodium hydroxide in water to obtain an aqueous solution, and mixing trimesoyl chloride and n-heptane to obtain an oil solution; immersing the membrane treated in step 3 in the aqueous solution, the oil solution, and the aqueous solution in turn to perform an interfacial polymerization reaction; washing and drying to obtain a PPTA composite nanofiltration membrane with an optimized pore size using a hydrogel mosaic structure.
[0011] As a preferred solution of the method for preparing the PPTA composite nanofiltration membrane with optimized pore size by using a hydrogel mosaic structure described in the present invention: the poly(p-phenylene terephthalamide) nanofiltration membrane base membrane uses a PET non-woven fabric as a support layer.
[0012] As a preferred embodiment of the method for preparing the PPTA composite nanofiltration membrane with optimized pore size by using a hydrogel mosaic structure of the present invention: the precursor solution is an anhydrous ethanol solution of tetraethyl titanate, and the concentration of the precursor solution is 5-8wt%.
[0013] As a preferred embodiment of the method for preparing the PPTA composite nanofiltration membrane with optimized pore size by using a hydrogel mosaic structure according to the present invention: in step 2, the hydrolysis time is 3 to 5 hours.
[0014] As a preferred embodiment of the method for preparing the PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure according to the present invention: in step 3, the silane coupling agent includes one of KH-550, KH-570 and KH-602.
[0015] As a preferred embodiment of the method for preparing the PPTA composite nanofiltration membrane with optimized pore size by using a hydrogel mosaic structure according to the present invention: in step 3, the concentration of the silane coupling agent solution is 0.5-1 wt %.
[0016] As a preferred embodiment of the method for preparing the PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure described in the present invention: in step 4, the membrane treated in step 3 is sequentially immersed in an aqueous solution for 2 to 3 minutes, an oily solution for 2 to 3 minutes, and an aqueous solution for 2 to 3 minutes.
[0017] As a preferred embodiment of the method for preparing the PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure according to the present invention: in step 4, the molar ratio of piperazine-2-carboxylic acid to sodium hydroxide is 1:1; and the mass concentration of piperazine-2-carboxylic acid is 0.5-1 wt%.
[0018] As a preferred embodiment of the method for preparing the PPTA composite nanofiltration membrane with optimized pore size by using a hydrogel mosaic structure of the present invention: in step 4, the concentration of trimesoyl chloride is 0.1-0.2 wt %.
[0019] As a preferred embodiment of the method for preparing the PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure according to the present invention: in step 4, the washing includes washing with ethanol.
[0020] Beneficial effects of the present invention: Compared with the PPTA composite nanofiltration membrane without mosaic structure pore size optimization, the pore size distribution and structural stability of the PPTA nanofiltration membrane prepared by the present invention are significantly improved under the optimization of the hydrogel mosaic structure, and the permeation flux and interception are significantly improved; the nanofiltration membrane with optimized pore size prepared by the present invention can be used in the field of membrane separation, for example, in the water treatment industry for drinking water purification, industrial water treatment, seawater desalination and wastewater treatment, to improve water quality to meet the needs of different uses. It can also be used in the biopharmaceutical field and the chemical dye industry, etc., and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment, wherein:
[0022] Figure 1 This is a picture of the PPTA composite nanofiltration membrane prepared in Example 4. DETAILED DESCRIPTION
[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.
[0024] Embodiment 1:
[0025] A method for preparing a PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure comprises the following steps:
[0026] (1) Prepare a PPTA (poly(p-phenylene terephthalamide)) base film supported by PET non-woven fabric according to a standardized process (refer to Preparation and Characterization of Poly(p-phenylene terephthalamide) Porous Film, Wang Chun, 2014), with a base film thickness of 300 μm;
[0027] (2) The PPTA base film was fixed in a pressurizing device, the nitrogen pressurizing pressure was set to 4.0 MPa, and an anhydrous ethanol solution of tetraethyl titanate with a tetraethyl titanate concentration of 5.0 wt% was pressed into the membrane pool. The solution penetration time was 6 min, and a PPTA porous membrane was obtained;
[0028] (3) placing the completely permeated PPTA porous membrane obtained in step (2) in a hydrolysis solution prepared by 80% anhydrous ethanol and 20% deionized water for 3 hours, wherein the water in the hydrolysis solution penetrates into the membrane pores and hydrolyzes tetraethyl titanate, and as the hydrolysis proceeds, TiO2 hydrogel is formed in the membrane pores;
[0029] (4) after the reaction in step (3) is completed, a layer of 0.5 wt% KH550 silane coupling agent aqueous solution is uniformly coated on the surface of the base film;
[0030] (5) 0.5 wt% piperazine-2-carboxylic acid (CPIP) and an equal molar ratio of sodium hydroxide are dissolved in pure water to obtain an aqueous solution required for an interfacial polymerization (IP) reaction, and 0.1 wt% trimesoyl chloride (TMC) is added to n-heptane to obtain an oil solution required. The base film is immersed in the aqueous solution for 2 minutes and then immersed in the oil solution for 3 minutes, and the interfacial polymerization (IP) reaction can be completed on the surface of the base film.
[0031] (6) The nanofiltration membrane was fully rinsed with anhydrous ethanol, and then clamped on a shaping plate for drying. After completion, it was immersed in pure water for 12 hours to prepare a new nanofiltration membrane with an IP layer polymerized on the basis of pore size optimization; the above experiment was repeated many times and corresponding performance tests were performed. After testing, the average pore size of the nanofiltration membrane base membrane with a hydrogel mosaic structure prepared in this embodiment was 0.16 μm, the pore size distribution range was 0.12-0.27 μm, and the water permeation flux of the PPTA composite nanofiltration membrane was 135 Lm -2 h -1 MPa -1 The water flux attenuation rate after 10 measurements was 12%, and the water flux attenuation rate after 15 measurements was 16%. The 30-minute retention rates of 1g / LNa2SO4 and 1g / LMgSO4 tested at room temperature and a pressure of 0.45MPa were 90% and 81%, respectively.
[0032] Step (1) The water permeation flux of the PPTA-based membrane is 326 Lm -2 h -1 MPa -1 At room temperature and pressure of 0.45MPa, the 30-minute retention rates of 1g / L Na2SO4 and 1g / LMgSO4 were 24% and 22% respectively.
[0033] Embodiment 2:
[0034] A method for preparing a PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure comprises the following steps:
[0035] (1) A PPTA (poly(p-phenylene terephthalamide)) base film supported by a PET nonwoven fabric was prepared according to a standardized process, and the base film thickness was 300 μm;
[0036] (2) The PPTA base film was fixed in a pressurizing device, the nitrogen pressurizing pressure was set to 4.0 MPa, and an anhydrous ethanol solution of tetraethyl titanate with a tetraethyl titanate concentration of 8.0 wt% was pressed into the membrane pool. The solution penetration time was 6 min, and a PPTA porous membrane was obtained;
[0037] (3) placing the completely permeated PPTA porous membrane obtained in step (2) in a hydrolysis solution prepared by 80% anhydrous ethanol and 20% deionized water for 3 hours, wherein the water in the hydrolysis solution penetrates into the membrane pores and hydrolyzes tetraethyl titanate, and as the hydrolysis proceeds, TiO2 hydrogel is formed in the membrane pores;
[0038] (4) after the reaction in step (3) is completed, a layer of 0.5 wt% KH550 silane coupling agent aqueous solution is uniformly coated on the surface of the base film;
[0039] (5) 0.5 wt% piperazine-2-carboxylic acid (CPIP) and an equal molar ratio of sodium hydroxide are dissolved in pure water to obtain an aqueous solution required for an interfacial polymerization (IP) reaction, and 0.1 wt% trimesoyl chloride (TMC) is added to n-heptane to obtain an oil solution required. The base film is immersed in the aqueous solution for 2 minutes and then immersed in the oil solution for 3 minutes, and the interfacial polymerization (IP) reaction can be completed on the surface of the base film.
[0040] (6) The nanofiltration membrane was fully rinsed with anhydrous ethanol, and then clamped on a shaping plate for drying. After completion, it was immersed in pure water for 12 hours to prepare a new nanofiltration membrane with an IP layer polymerized on the basis of pore size optimization; the above experiment was repeated many times and corresponding performance tests were performed. After testing, the average pore size of the nanofiltration membrane base membrane with a hydrogel mosaic structure prepared in this embodiment was 0.275 μm, the pore size distribution range was 0.24N0.354 μm, and the water permeation flux of the PPTA composite nanofiltration membrane after the pore size was optimized was 116 Lm -2 h -1 MPa -1 The water flux attenuation rate after 10 measurements was 11%, and the water flux attenuation rate after 15 measurements was 15%. The 30-minute retention rates of 1g / LNa2SO4 and 1g / LMgSO4 tested at room temperature and a pressure of 0.45MPa were 92% and 83% respectively, and they also had good solvent resistance.
[0041] Compared with Example 1, the solution concentration of the precursor used in Example 2 is higher, which provides sufficient reaction raw materials for the subsequent condensation reaction and more fully modifies the macropores in the base membrane. Therefore, the water permeation flux is reduced compared with Example 1.
[0042] Embodiment 3:
[0043] A method for preparing a PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure comprises the following steps:
[0044] (1) A PPTA (poly(p-phenylene terephthalamide)) base film supported by a PET nonwoven fabric was prepared according to a standardized process, and the base film thickness was 300 μm;
[0045] (2) The PPTA base film was fixed in a pressurizing device, the nitrogen pressurizing pressure was set to 4.0 MPa, and an anhydrous ethanol solution of tetraethyl titanate with a tetraethyl titanate concentration of 8.0 wt% was pressed into the membrane pool. The solution penetration time was 6 min, and a PPTA porous membrane was obtained;
[0046] (3) placing the completely permeated PPTA porous membrane obtained in step (2) in a hydrolysis solution prepared by 80% anhydrous ethanol and 20% deionized water for 3 hours, wherein the water in the hydrolysis solution penetrates into the membrane pores and hydrolyzes tetraethyl titanate, and as the hydrolysis proceeds, TiO2 hydrogel is formed in the membrane pores;
[0047] (4) after the reaction in step (3) is completed, a layer of 0.5 wt% KH550 silane coupling agent aqueous solution is uniformly coated on the surface of the base film;
[0048] (5) 0.5wt% piperazine-2-carboxylic acid (CPIP) and an equal molar ratio of sodium hydroxide are dissolved in pure water to obtain the aqueous phase solution required for the interfacial polymerization (IP) reaction, and 0.1wt% trimesoyl chloride (TMC) is added to n-heptane to obtain the required oil phase solution. The base film is sequentially immersed in the corresponding solutions in the order of aqueous phase-oil phase-aqueous phase, that is, the base film is first immersed in the aqueous phase solution for 2 minutes, then immersed in the oil phase solution for 3 minutes, and then immersed in the aqueous phase solution for 2 minutes, and the interfacial polymerization (IP) reaction is completed on the surface of the base film;
[0049] (6) The nanofiltration membrane was fully rinsed with anhydrous ethanol, and then clamped on a shaping plate for drying. After completion, it was immersed in pure water for 12 hours to prepare a new nanofiltration membrane with an IP layer polymerized on the basis of pore size optimization; the above experiment was repeated many times and corresponding performance tests were performed. After testing, the average pore size of the nanofiltration membrane base membrane with a hydrogel mosaic structure prepared in this embodiment was 0.253 μm, the pore size distribution range was 0.22-0.36 μm, and the permeation flux of the PPTA composite nanofiltration membrane after optimizing the pore size was 216 Lm -2 h -1 MPa -1 The water flux attenuation rate after 10 measurements was 11%, and the water flux attenuation rate after 15 measurements was 16%. The 30-minute retention rates of 1g / LNa2SO4 and 1g / LMgSO4 tested at room temperature and a pressure of 0.45MPa were 95% and 87%, respectively.
[0050] In this embodiment, based on Example 2, the IP layer is prepared in the order of water phase-oil phase-water phase infiltration in the preparation process of interfacial polymerization. Due to the additional water-oil interaction, the IP layer is more fully polymerized on the surface of the base membrane, and the pleated structure for liquid passage is increased. This is one of the main reasons why the composite nanofiltration membrane prepared in this embodiment has better retention and water permeation flux than that in Example 1 and Example 2.
[0051] Embodiment 4:
[0052] A method for preparing a PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure comprises the following steps:
[0053] (1) A PPTA (poly(p-phenylene terephthalamide)) base film supported by a PET nonwoven fabric was prepared according to a standardized process, and the base film thickness was 300 μm;
[0054] (2) The PPTA base film was fixed in a pressurizing device, the nitrogen pressurizing pressure was set to 4.0 MPa, and an 8.0 wt% anhydrous ethanol solution of tetraethyl titanate was pressed into the membrane pool at room temperature. The solution penetration time was 6 min, and a PPTA porous membrane was obtained;
[0055] (3) placing the completely permeated PPTA porous membrane obtained in step (2) in a hydrolysis solution prepared by 95 wt% ethanol and 5 wt% deionized water for 3 h, wherein the water in the hydrolysis solution penetrates into the membrane pores and hydrolyzes tetraethyl titanate, and as the hydrolysis proceeds, TiO2 hydrogel is formed in the membrane pores;
[0056] (4) after the reaction in step (3) is completed, a layer of 0.5 wt% KH550 silane coupling agent aqueous solution is uniformly coated on the surface of the base film;
[0057] (5) 0.5wt% piperazine-2-carboxylic acid (CPIP) and an equal molar ratio of sodium hydroxide are dissolved in pure water to obtain the aqueous phase solution required for the interfacial polymerization (IP) reaction, and 0.1wt% trimesoyl chloride (TMC) is added to n-heptane to obtain the required oil phase solution. The base film is sequentially immersed in the corresponding solutions in the order of aqueous phase-oil phase-aqueous phase, that is, the base film is first immersed in the aqueous phase solution for 2 minutes, then immersed in the oil phase solution for 3 minutes, and then immersed in the aqueous phase solution for 2 minutes, and the interfacial polymerization (IP) reaction is completed on the surface of the base film;
[0058] (6) The nanofiltration membrane obtained in step (5) was fully rinsed with anhydrous ethanol, and then clamped on a shaping plate for drying. After completion, it was immersed in pure water for 12 hours to obtain a new nanofiltration membrane with an IP layer polymerized on the basis of pore size optimization; the above experiment was repeated many times and corresponding performance tests were performed. After testing, the average pore size of the nanofiltration membrane base membrane with a hydrogel mosaic structure prepared in this embodiment was 0.253 μm, the pore size distribution range was 0.22 to 0.36 μm, and the water permeation flux of the PPTA composite nanofiltration membrane after the pore size was optimized was 252 Lm -2 h -1 MPa -1 The water flux attenuation rate after 10 measurements was 7%, and the water flux attenuation rate after 15 measurements was 12%. The 30-minute retention rates of 1g / LNa2SO4 and 1g / LMgSO4 tested at room temperature and a pressure of 0.45MPa were 96.5% and 88.6% respectively, and they showed good solvent resistance and acid and alkali corrosion resistance.
[0059] Based on Example 3, this example improves the ratio of the hydrolysis reaction liquid, reduces the proportion of pure water in the reaction liquid, and thus slows down the hydrolysis rate of the precursor, making the condensed gel particles more uniform and reducing the stacking and aggregation of the gel particles. Therefore, how to effectively distribute the gel particles evenly in the pores is one of the key links of this experiment.
[0060] Comparative Example 1:
[0061] Compared with Example 4, no pore size modification is performed and interfacial polymerization is directly carried out on the PPTA porous membrane, that is, the process of steps (2) and (3) is not performed. The rest of the preparation method (steps 1, 4, 6) is the same as Example 4.
[0062] After corresponding performance tests, the average pore size of the nanofiltration membrane prepared in this embodiment is 0.483 μm, the pore size distribution range is 0.21-0.68 μm, and the permeation flux of the PPTA composite nanofiltration membrane after optimizing the pore size is 232 Lm -2 h -1 MPa -1 The water flux attenuation rate after 10 measurements was 38%, and the water flux attenuation rate after 15 measurements was 44%. The 30-minute retention rates of 1g / LNa2SO4 and 1g / LMgSO4 tested at room temperature and a pressure of 0.45MPa were 36% and 34% respectively.
[0063] Since the PPTA porous membrane has not been modified with a hydrogel embedded structure, the large pores originally existing on the base membrane still exist after interfacial polymerization. Although it has a good water permeation flux, its retention performance is poor.
[0064] Comparative Example 2:
[0065] Compared with Example 4, in step (2), the precursor solution is not pressed into the membrane pores by pressurization, but the PPTA porous membrane is directly immersed in 8wt% tetraethyl titanate-anhydrous ethanol solution, that is, step (2) is not pressurized, and the rest of the preparation method is the same as Example 4.
[0066] After corresponding performance tests, the average pore size of the nanofiltration membrane prepared in this embodiment is 0.453 μm, the pore size distribution range is 0.22-0.65 μm, and the permeation flux of the PPTA nanofiltration membrane after optimizing the pore size is 195 Lm -2 h -1 MPa -1 The water flux attenuation rate after 10 measurements was 37%, and the water flux attenuation rate after 15 measurements was 42%. The 30-minute retention rates of 1g / LNa2SO4 and 1g / LMgSO4 tested at room temperature and a pressure of 0.45MPa were 43% and 37%, respectively.
[0067] Because the precursor solution was not pressed into the pores of the PPTA porous membrane by bubble point pressure, the condensed TiO2 gel particles only floated on the surface of the membrane and did not penetrate into the pores of the membrane to achieve the purpose of optimizing the pore size. In addition, since some gel particles were solidified on the surface of the membrane, the surface of the membrane was uneven, which also had an adverse effect on the subsequent interfacial polymerization operation and preparation.
[0068] In addition, experimental research has found that the pressurization pressure should be close to or slightly greater than the minimum pore pressure. Too little pressure cannot press the precursor solution into the pore.
[0069] Comparative Example 3:
[0070] Compared with Example 4, the hydrolysis solution (a mixture of 95% anhydrous ethanol and 5% deionized water) in step (3) was replaced with pure deionized water, and the remaining conditions and preparation process were the same as those in Example 4.
[0071] After corresponding performance tests, the average pore size of the nanofiltration membrane with a hydrogel mosaic structure prepared in this embodiment is 0.31 μm, the pore size distribution range is 0.20-0.44 μm, and the permeation flux of the PPTA nanofiltration membrane after optimizing the pore size is 23 Lm -2 h -1 MPa -1 The water flux attenuation rate after 10 measurements was 22%, and the water flux attenuation rate after 15 measurements was 27%. The 30-minute retention rates of 1g / LNa2SO4 and 1g / LMqSO4 were 33% and 27% respectively at room temperature and pressure of 0.45MPa.
[0072] Since the reaction liquid was replaced with pure water, the concentration ratio of the reactants was increased, thereby increasing the reaction rate of the precursor and water, causing serious stacking and aggregation of gel particles. The aggregated large TiO2 particles formed blockage in the pores, which in turn caused a serious decrease in the water seepage flux.
[0073] In addition, experimental research has found that the proportion of pure water in the hydrolyzate is crucial to whether the gel particles can be evenly distributed in the membrane pores. Too high a water proportion will cause pore congestion.
[0074] Comparative Example 4:
[0075] Compared with Example 4, KH590 silane coupling agent is selected in step (4), and the remaining conditions and preparation process are the same as those in Example 4.
[0076] After corresponding performance tests, the average pore size of the nanofiltration membrane base membrane with a hydrogel mosaic structure prepared in this embodiment is 0.29 μm, the pore size distribution range is 0.20-0.43 μm, and the permeation flux of the PPTA nanofiltration membrane after optimizing the pore size is 173 Lm -2 h -1 MPa -1 The water flux attenuation rate after 10 measurements was 13%, and the water flux attenuation rate after 15 measurements was 24%. The 30-minute retention rates of 1g / LNa2SO4 and 1g / LMgSO4 tested at room temperature and pressure of 0.45MPa were 82% and 71% respectively.
[0077] It was found that the silane coupling agent without amino group resulted in insufficient bonding between the interfacially polymerized IP layer and the porous film of PPTA, which also caused the core performance of the nanofiltration membrane produced in this embodiment to decline. In addition, it was found through experimental exploration that the silane coupling agent containing amino group has a strong adaptability to the PPTA porous membrane and can better connect the membrane layer and the IP layer.
[0078] Comparative Example 5:
[0079] (1) preparing a PPTA (poly(p-phenylene terephthalamide)) base film supported by a PET nonwoven fabric, the base film thickness being 300 μm;
[0080] (2) adding deionized water in an equal molar ratio to an anhydrous ethanol solution of tetraethyl titanate with a concentration of 5.0 wt % of tetraethyl titanate, and allowing the reaction to proceed for 0.5 h;
[0081] (3) filtering the reaction solution in step (2) to obtain a TiO2 hydrogel;
[0082] (4) The gel particles in step (3) are evenly coated on the surface of the base film and then air-dried for 2 hours;
[0083] (5) 0.5 wt% piperazine-2-carboxylic acid (CPIP) and an equal molar ratio of sodium hydroxide are dissolved in pure water to obtain an aqueous phase solution required for an interfacial polymerization (IP) reaction, and 0.1 wt% trimesoyl chloride (TMC) is added to n-heptane to obtain a required oil phase solution. The treated base film is immersed in the aqueous phase solution for 2 minutes and then immersed in the oil phase solution for 3 minutes, and the interfacial polymerization (IP) reaction can be completed on the surface of the base film.
[0084] (6) The nanofiltration membrane was fully rinsed with anhydrous ethanol, and then clamped on a shaping plate for drying. After completion, it was immersed in pure water for 12 hours to prepare a new nanofiltration membrane with an IP layer polymerized on the basis of pore size optimization; the above experiment was repeated many times and corresponding performance tests were performed. After corresponding performance tests, the average pore size of the nanofiltration membrane base membrane prepared in this embodiment was 0.573 μm, the pore size distribution range was 0.21 to 0.68 μm, and the permeation flux of the PPTA nanofiltration membrane after the pore size optimization was 205 Lm -2 h -1 MPa -1 The water flux attenuation rate after 10 measurements was 32%, and the water flux attenuation rate after 15 measurements was 47%. The 30-minute retention rates of 1g / LNa2SO4 and 1g / LMgSO4 tested at room temperature and a pressure of 0.45MPa were 35% and 32%, respectively.
[0085] The TiO2 gel particles are coated onto the surface of the base film, but do not penetrate into the pores of the film to achieve the purpose of optimizing the pore size. In addition, the gel particles on the surface are not firmly bonded, which has an adverse effect on the subsequent interfacial polymerization operation and preparation, resulting in a low interception rate and poor durability.
[0086] Comparative Example 6:
[0087] Compared with Example 4, that is, in step (2), the 8 wt % tetraethyl titanate-anhydrous ethanol solution is changed to a 12 wt % tetraethyl titanate-anhydrous ethanol solution, and the rest of the preparation method is the same as that of Example 4.
[0088] After corresponding performance tests, the average pore size of the nanofiltration membrane prepared in this embodiment is 0.253 μm, the pore size distribution range is 0.14N0.32 μm, and the permeation flux of the PPTA nanofiltration membrane after optimizing the pore size is 75 Lm -2 h -1 MPa -1 The retention rates of 1g / L Na2SO4 and MgSO4 are 53% and 47% respectively.
[0089] Due to the use of an overly high concentration of precursor solution, the pores of the PPTA porous membrane are over-modified, which not only fills the large pores but also squeezes the pore space of the small pores, causing a serious decrease in the water permeation flux.
[0090] Comparative Example 7:
[0091] Compared with Example 4, the nitrogen pressurization pressure in step (2) was changed from 4.0 MPa to 5.0 MPa, and the rest of the preparation method was the same as that of Example 4.
[0092] After corresponding performance tests, the average pore size of the nanofiltration membrane prepared in this embodiment is 0.23 μm, the pore size distribution range is 0.12-0.325 μm, and the water permeation flux of the PPTA composite nanofiltration membrane after optimizing the pore size is 172 Lm -2 h -1 MPa -1 The water flux attenuation rate after 10 measurements was 18%, and the water flux attenuation rate after 15 measurements was 23%. The retention rates of 1g / L Na2SO4 and 1g / LMgSO4 were 87.5% and 73.6% respectively, and the solvent resistance was poor.
[0093] Due to the excessive nitrogen pressurization pressure, the precursor solution flows into the macropores of the PPTA porous membrane at a faster rate. Although there is still a certain modification effect, the excessive pressure will destroy the ridge and valley structure of the membrane pores, resulting in a certain decrease in its durability and solvent resistance.
[0094] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure, characterized in that: The following steps are included: Step 1: applying a pressure of 2.5-4.0 MPa to a poly(p-phenylene terephthalamide) nanofiltration membrane base film, immersing it in a 4-10 wt% precursor solution for 2-8 min to obtain a PPTA porous membrane; the precursor solution includes titanate or silicate; Step 2: placing the PPTA porous membrane obtained in step 1 in an 80-95% ethanol solution for hydrolysis to obtain a PPTA porous membrane with modified pore size; Step 3: coating a layer of silane coupling agent solution on the surface of the pore-modified PPTA porous membrane obtained in step 2; Step 4: dissolving piperazine-2-carboxylic acid and sodium hydroxide in water to obtain an aqueous solution, and mixing trimesoyl chloride and n-heptane to obtain an oil solution; immersing the membrane treated in step 3 in the aqueous solution, the oil solution, and the aqueous solution in turn to perform an interfacial polymerization reaction; washing and drying to obtain a PPTA composite nanofiltration membrane with an optimized pore size using a hydrogel mosaic structure.
2. The method for preparing a PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure according to claim 1, characterized in that: The poly(p-phenylene terephthalamide) nanofiltration membrane base film uses PET non-woven fabric as a supporting layer.
3. The method for preparing a PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure according to claim 1 or 2, characterized in that: The precursor solution is an anhydrous ethanol solution of tetraethyl titanate, and the concentration of the precursor solution is 5-8wt%.
4. The method for preparing a PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure according to claim 1 or 2, characterized in that: In step 2, the hydrolysis time is 3 to 5 hours.
5. The method for preparing a PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure according to claim 1 or 2, characterized in that: In step 3, the silane coupling agent includes one of KH-550, KH-570 and KH-602.
6. The method for preparing a PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure according to claim 5, characterized in that: In step 3, the concentration of the silane coupling agent solution is 0.5-1 wt %.
7. The method for preparing a PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure according to claim 1 or 2, characterized in that: In step 4, the membrane treated in step 3 is immersed in the aqueous solution for 2 to 3 minutes, the oily solution for 2 to 3 minutes, and the aqueous solution for 2 to 3 minutes in sequence.
8. The method for preparing a PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure according to claim 1 or 2, characterized in that: In step 4, the molar ratio of piperazine-2-carboxylic acid to sodium hydroxide is 1:1; and the mass concentration of piperazine-2-carboxylic acid is 0.5-1 wt%.
9. The method for preparing a PPTA composite nanofiltration membrane using a hydrogel mosaic structure to optimize pore size according to claim 1 or 2, characterized in that: In step 4, the concentration of trimesoyl chloride is 0.1-0.2 wt %.
10. The method for preparing a PPTA composite nanofiltration membrane with optimized pore size using a hydrogel mosaic structure according to claim 1 or 2, characterized in that: In step 4, the washing comprises washing with ethanol.
Citation Information
Patent Citations
External-pressure type charged hollow fiber nano-filtration membrane and preparation method therefor
CN102921318A
Preparation method of anti-pollution polysulfone composite nanofiltration membrane for filtering water body
CN111790274A
Composite nanofiltration membrane as well as preparation method and application thereof
CN114984785A
Preparation method of homogeneous fiber reinforced PPTA hollow fiber nanofiltration membrane
CN115532077A
Solvent-resistant aramid nanofiltration membrane as well as preparation method and application thereof
CN117797652A